Structural and Conduction Studies of Solid Biopolymer Electrolytes System Based on Carboxymethyl Cellulose - N.A.M. Noor; M.I.N. Isa (American-Eurasian Network for Scientific Information publisher, 2024)
This present work discovered on a new proton conducting solid biopolymer electrolytes (SBE) based on biopolymer-carboxymethyl cellulose (CMC) complexed with various concentrations of ammonium thiocyanate (NH4SCN). In the polymer-salt complexes system has been prepared via solution-casting method. The ionic conductivity study of the samples was measured using Electrical Impedance Spectroscopy (EIS) and the highest ionic conductivity at room temperature was obtained at 6.48 x 10-5 Scm-1 for the sample containing with 25 wt.% NH4SCN. The temperature dependence of ionic conductivity of the CMC-NH4SCN SBE system follow Arrhenius law due to increases of conductivity with increment of NH4SCN concentrations. Fourier Transform Infrared (FTIR) spectroscopy was done to study the complexation between CMC and NH4SCN. X-ray diffraction study inferred that the samples containing 25 wt.% NH4SCN exhibits highest amorphous nature which revealed that highest conductivity in CMC-NH4SCN SBE system.